Sperm biology and male reproductive health - Ricardo P. Bertolla (Nature Portfolio, 2020)
Sperm are unique cells, produced through the complex and precisely orchestrated process of spermatogenesis, in which there are a number of checkpoints in place to guarantee delivery of a high-quality and high-fidelity DNA product. On the other hand, reproductive pressure in males means that to produce more is, in very general terms, to perform better. Balancing quantity and quality in sperm production is thus a delicate process, subject to specific cellular and molecular control mechanisms, and sensitive to environmental conditions, that can impact fertility and offspring health. This Collection is focused on these aspects of sperm biology, as well as their impact on reproductive performance and male infertility.